IMPLEMENTATION OF MODELING TECHNIQUES ON SOCIAL SKILLS WITH INTELLECTUAL DISABILITY - R. Enkeu Agiati; Suhendar Suhendar (Politeknik Kesejahteraan Sosial Bandung, 2018)
Social skills refer to the ability of people with intellectual disabilities in expressing emotions both verbally and non-verbally that can be accepted or responded to, as well as beneficial to themselves and others. The purpose of this study was to obtain an empirical overview and conduct analysts about: 1) Characteristics of respondents, 2) Overview of social skills before applying modeling techniques, and 3) Overview of social skills after modeling techniques. The method used is quantitative method with Single Subject Design (SSD). Data collection techniques used questionnaires, observation, and documentation studies. The source of this research data is primary and secondary sources. The sampling technique used is Simple Random Sample. The validity of the measuring instrument is to test the validity of the product moment technique, while the reliability test of the measuring instrument uses Alpha Cronbach's internal concistency analysis method. The analytical technique is quantitative. The results of the study show that the implementation of modeling techniques influences the social skills of people with intellectual disabilities.